Philosophie als Transzendieren: der Aufstieg zum höchsten Prinzip bei Platon und Plotin - Halfwassen, Jens (Bochumer philosophisches Jahrbuch für Antike und Mittelalter, 1998)
Transcendent thinking as a basic feature of metaphysical philosophy has always claimed to be more than a mere cognition of reality in terms of its phenomena. Transcendent philosophy intends to consider reality from the perspective of a fundamental ground transcending the reality ordered - by that ground. Plato, who created the very notion of philosophy, described the love of wisdom as an ascent to the absolutely transcendent One and Good, which he believed to be the principle and source of all being. Plotinus both took over and renewed the Platonic view of philosophy as transcendent - thinking. In his view, the philosopher can only relate to that principle which transcends even thinking itself by practicing a mystical philosophy and thereby leaving behind his own dialectical thinking.
Gesehen am 04.11.2020